LIQUID LIMIT VALUES OBTAINED BY DIFFERENT TESTING METHODS - Kollaros, G. (Bulletin of the Geological Society of Greece, 2016)
Specifications in European countries include a variety of methods for determining the liquid limit based on Casagrande type devices and on the fall cone penetrometer. The results of a comparative study of the liquid limits determined using these two fall-cone methods are presented for lime stabilized soil. Soil material sampled in the area of Evros Regional Unit has been stabilized with lime in order to enhance its engineering characteristics. The soil and the soil-lime mixtures subjected in Atterberg limit testing. The liquid limit values were correlated through a linear regression analysis with the rest of the consistency limits of both the natural soil and its mixtures with various lime contents. The correlation coefficients in all cases were high, with those referring to results obtained by the Casagrande method to be dominant. The comparison of liquid limit values determined by either method showed that there is a systematically good correlation between them, with the decrease rate in function of the lime content in the mixture to be more intense in the case of the drop-cone procedure. There is a need for a universal specification for the determination of the consistency limits.